Compressive strength of binary and ternary blended cement mortars containing fly ash and silica fume under autoclaved curing - Wongkeo W. (2017)
Cement industry is a one of the major sources of environmental pollution therefore the reduction of cement demand should be improved. Fly ash and silica fume is a by-product of industries and it should be reused to reduce the waste pollution. Thus, this study investigated the use of fly ash and silica fume as a cement replacement in binary and ternary blended cements on compressive strength and physical properties of mortar. Autoclaved curing at 130 °C and 20 psi of pressure for 9 h was used in this study. The results show that the compressive strength of binary blended cement mortar with FA tends to decrease with increased FA replacement and shows compressive strength lower than PC control. However, compressive strength of binary blended cement mortar with SF was improved and shows compressive strength higher than that of PC control. The compressive strength of ternary blended cement mortar was higher than binary blended cement at the same level replacement and it increases with increased SF replacement. Moreover, ternary blended cement mortar containing 10%SF by weight contribute in giving compressive strength higher than PC control. The incorporation of FA with SF can enhance workability of blended cement mortar containing only SF replacement. © (2012) Trans Tech Publications, Switzerland.